Protection of Plywood in Storage in Godowns Against Lyctus Beetles by Treatment with Dichloro-diphenyl-trichloroethane (D.D.T.) and Benzene Hexachloride (B.H.C.) - Chatterjee, P. N. (Indian Forester, 1953)
No abstract